Post-anesthesia care : symptoms, diagnosis, and management - Heitz, James W. (Cambridge, United Kingdom : Cambridge University Press, 2016)
"The initial hours after surgery are a critical time in the care of the surgical patient. Familiarity with the clinical presentation of perioperative complications is important to achieving optimal outcomes. By taking an approach to complications based upon signs and symptoms seen in the early post-operative period among adult patients undergoing non-cardiac surgery, this book aids the practitioner in the clinical management of surgical patients during the often turbulent hours after surgery. After a brief introduction to PACU organization, this manual discusses the common and most serious symptoms encountered in the post-operative patient, giving guidance on diagnosis of the underlying disorder and the treatment options available. The book also includes chapters dedicated to subspecialty patients, including patients requiring post-operative mechanical ventilation, pediatric patients, patients with implantable cardiac devices, morbidly obese patients and the complex pain patient. This practical manual is essential reading for all practitioners working in the PACU environment"--Provided by publisher
Machine generated contents note: Preface; Part I. Introduction: 1. Recovery: physiological challenges Niels D. Martin and James W. Heitz; 2. Recovery: goals and standards Philippa Ratcliffe; Part II. Signs and Symptoms: 3. Hypertension James W. Heitz; 4. Hypotension James W. Heitz; 5. Dysrhythmia Eric Massey and Stephen O. Bader; 6. Chest pain Jeremy L. Hensley and Stephen O. Bader; 7. ECG changes Adam W. Green and Stephen O. Bader; 8. Heart failure Glen D. Quigley and Elia S. Elia; 9. Hypoxia Gadi Arzanipour and James W. Heitz; 10. Wheezing and stridor Michelle McMaster and James W. Heitz; 11. Tachypnea and hypopnea Erika Davis and Marc Fisicaro; 12. Dyspnea Erika Davis and Marc Fisicaro; 13. Dysphonia and airway trauma Megan J. Sharpe and Julie P. Ma; 14. Fever, hyperpyrexia and hyperthermia Andrea M. Hages and James W. Heitz; 15. Hypothermia Min J. Chun and Lisa Luyun; 16. Hypoglycemia Brian Hipszer, James W. Heitz and Jeffrey I. Joseph; 17. Hyperglycemia in the PACU Boris Mraovic and Jeffrey I. Joseph; 18. Electrolyte disorders Michael Jon Williams; 19. Nausea and vomiting James W. Heitz; 20. Pruritus James W. Heitz; 21. Weakness Donald Baumann; 22. Movement disorders Nicole Renaldi; 23. Limb paralysis James W. Heitz; 24. Rigidity Ashley Caplan and James W. Heitz; 25. Seizure James W. Heitz and Michelle Beam; 26. Delirium James W. Heitz; 27. Headache James W. Heitz; 28. Delayed emergence Jon Zhou and James W. Heitz; 29. Crying Michelle Beam and James W. Heitz; 30. Rash David Beausang and Michelle Beam; 31. Jaundice George Hsu and James W. Heitz; 32. Visual disturbance James W. Heitz; 33. Neuropathy Brian Lai and John T. Wenzel; 34. Shivering James W. Heitz; 35. Oliguria and postoperative urinary obstruction James W. Heitz; 36. Polyuria James W. Heitz; 37. Abnormal urine color James W. Heitz; 38. Pain Benjamin Vaghari, Jaime Baratta and Kishor Gandhi; 39. Shoulder pain Jordan E. Goldhammer; 40. Anemia Elizabeth Wolo and James W. Heitz; 41. Hemorrhage Jeremy L. Hensley and Stephen O. Bader; 42. Intraoperative awareness Michelle Beam and James W. Heitz; Part III. Special Considerations: 43. Special considerations for mechanical ventilation Yousef Hamdeh, Zara Y. Mergan and James W. Heitz; 44. Special considerations for the pediatric patient Peter Jonathan Gambino, Allan F. Simpao and Zvi Grunwald; 45. Special consideration for the pregnant patient after non-obstetric surgery Suzanne Huffnagle and H. Jane Huffnagle; 46. Special considerations for the cardiac patient with implanted devices Ryan P. Maxwell and Jordan E. Goldhammer; 47. Special considerations for the morbidly obese patient Emily J. MacKay and Michele Mele; 48. Special considerations for the renal failure patient Eric S. Schwenk; 49. Special considerations for pain management Benjamin Vaghari, Jaime Baratta and Kishor Gandhi; 50. PACU emergencies Robert F. Olszewski, Jr; Index
Includes bibliographical references and index
Keywords: Postoperative care; Postoperative Care; Recovery Room -- organization & administration; Anesthesiology -- trends; Print books